INFECTIOUS DISEASES OF THE NERVOUS SYSTEM IN CHILDREN AND ITS COMPLICATIONS - Polathojayeva Malika Rustamovna (International Scientific and Current Research Conferences, 2022)
The following article provides information on medical-pedagogical-petrological events in children's nerves and neuropsychological complications in children, and the clinical manifestations of children's neuropsychological complications.